Occidentalism at War: Al-Qaida’s Resistance Rhetoric (Altre Modernità, 2012)
Analysis of resistance groups active in the War on Terror provides case-studies for an examination of Occidentalism. Al-Qaida constructs a West both homogeneously and pejoratively in order to represent the self as a single Islamic nation under attack from a barbarian other. Concerned with propagating their narrative, al-Qaida considers the media battle to be at the forefront of their efforts. Yet global dissemination of their message is double-edged: positively, it can inspire disparate would-be jihadists; negatively, it opens up the discourse to examination in West. The discourse is studied, dissected and ultimately incorporated into the Western knowledge structure.